Hypoxia enhances antitumor activity of dichloroacetate - Kolesnik, D.L.; Pyaskovskaya, O.N.; Boichuk, I.V.; Solyanik, G.I. (Experimental Oncology, 2014)
It is known that glycolysis contributes to the survival of tumor cells by providing them with energetic and plastic substrates. Dichloroacetate (DCA) as inhibitor of kinase pyruvate dehydrogenase shifts balance of energy metabolism of tumor cells from aerobic glycolysis towards oxidative phosphorylation. The aim of the study was to investigate cytostatic/cytotoxic effect of DCA on glioma C6 cells at the conditions of different oxygenation of the cell incubation medium. Materials and Methods: DCA action on glioma C6 cells was investigated upon the conditions of normoxia, hypoxia (1% of oxygen) and hyperoxia (30% and 95% of oxygen) in vitro. The number and viability of tumor cells were assessed using trypan blue dye-exclusion test. Apoptosis was determined using dye Hoechst 33258. Lactate production by tumor cells was determined by enzymatic method using lactate dehydrogenase. Cell cycle distribution was studied using flow cytometry. Reactive oxygen species (ROS) content was evaluated using 2´,7´-dichlorofluorescein diacetate. Results: By the data of in vitro cytotoxicity, upon hypoxia IC50 value of DCA was three times lower (p < 0.05) than that upon normoxic conditions (18.2 ± 3.9 mM vs. 51.2 ± 8.1 mM). Hypoxia itself enhanced the ROS production in glioma cells by 113.5% (p < 0.05) that correlated with increase of apoptosis by 292% (p < 0.05). In hypoxic glioma C6 cells DCA did not significantly influence the ROS production, but decreased hypoxia-induced apoptosis by 3.5–6.5 times (p < 0.05) and significantly increased cell death rates via necrosis (p < 0.05). In contrast to hypoxia, upon the conditions of hyperoxia IC50 values for DCA did not differ from the corresponding values upon the normoxia conditions and at 30% and 95%oxygen content were equal to 35.8 ± 7.2 mM and 42.3 ± 5.1 mM respectively. Conclusion: According to the obtained results, hypoxia enhances cytostatic/cytotoxic effects of DCA in glioma C6 cells via high level of DCA-induced necrosis of tumor cells and hypoxia-induced ROS hyperproduction. Key Words: dichloroacetate, glioma C6, hypoxia, hyperoxia, reactive oxygen species, apoptosis.